Provision of ultraviolet basking lights to indoor housed tropical birds and their effect on suspected vitamin D3 deficiency - Drake, Gabby Jeanne-Clare; Shea, Robyn L; Fidgett, Andrea; Lopez, Javier; Christley, Robert M (Journal of Zoo and Aquarium Research, 2017)
Vitamin D deficiency (measured as 25(OH)D3) can occur if birds are fed a vitamin D deficient diet and do not have access to ultraviolet B light (UVB). This can result in eggs with deficient yolks and consequent metabolic bone disease (MBD) in chicks. In this study, hypovitaminosis D was suspected in 31 adult birds, from five orders, housed indoors long-term without prior access to UVB light. The study aimed to assess the effect of providing UVB basking lights on their vitamin D status and incidence of MBD in chicks. It also aimed to assess whether the birds would access the UVB provided. Breeding and pathology records were analysed, and birds were blood tested for 25(OH)D3 before, and 12 months after, being provided with access to UVB basking lights. The area of perching with UVB irradiance was filmed before and after the UVB basking lights were switched on. There was a significant increase in 25(OH)D3 after 12 months of UVB provision from a mean of 9.3 nmol/L to 14.2 nmol/L (p = 0.001, CI = 2.35 to 9.47). Annual incidence of metabolic bone disease in chicks dropped from an average of 14.4% over the three years prior to UVB provision to 2.8% in the two years afterwards, although this reduction was not statistically significant. Birds appeared to actively seek the basking spots and significantly increased the proportion of time spent in the area of UVB irradiance (p = 0.02). No correlation was found between the total amount, or change in time spent in the UVB area and the final, or change in individual birds circulating 25(OH)D3 levels. These results show that indoor housed birds will bask in UVB light if provided and this radiation can increase vitamin D levels of the birds, which may prevent MBD in their offspring.